Origami‐Inspired 3D Interconnected Molybdenum Carbide Nanoflakes. Issue 6 (15th January 2018) - Koizumi, Ryota; Ozden, Sehmus; Samanta, Atanu; Alves, Ana Paula P.; Mishra, Avanish; Ye, Gonglan; Silva, Glaura G.; Vajtai, Robert; Singh, Abhishek K.; Tiwary, Chandra S.; Ajayan, Pulickel M.
Abstract: High‐temperature stable transition metal carbides are one of the promising classes of materials for next‐generation energy applications such as water splitting catalysis and electrodes for energy storage devices. Herein, origami‐like molybdenum carbide flakes with interfacially connected structures in various orientations using an easily scalable chemical vapor deposition method are synthesized. Interestingly, each individual flake of similar orientation is interconnected across different planes. The interconnected architectures are found to be highly elastic and behave in a sponge‐like manner. In addition, the surface energy of each plane is calculated using the first‐principle density functional theory. The molybdenum carbide shows excellent activity for the hydrogen evolution reaction, with the onset over potential occurring around −16 to −25 mV with high stability. The material is used as an electrode for supercapacitors as a second demonstration. The supercapacitor constructed with polypyrrole reaches the specific capacitance of ≈279 F g −1 at a current density of 0.5 A g −1 . Abstract : Origami‐like interconnected molybdenum carbide flakes are synthesized using an easily scalable chemical vapor deposition method. These oriented Mo2 C‐interconnected flakes are demonstrated for hydrogen evolution reactions (HER) activity and supercapacitor applications. The onset over potential of Mo2 C flakes is around −16 to −25 mV with high stability, and the specific capacitance is ≈279 F g −1 at a current density of 0.5 A g −1 .